Quality and Economics of Summer Sesame (Sesamum indicum L.) as Influenced by Irrigation and Nutrient Levels - De, P. S.; Bhale, V. M.; Khadse, V. A. (International Journal of Bio-resource and Stress Management, 2023)
A field study aimed to evolve efficient and economically viable irrigation schedule and nutrient management for improving quality and economics of summer sesame var. AKT 101 was conducted on clay-loam soil during summer season of 2010. Irrigation applied at 1.0 IW/CPE resulted in higher oil yield ha-1 whereas, irrigation at 0.8 IW/ CPE gave maximum returns with B:C ratio. Among the nutrient levels, each successive dose from 50 to 150% RDF increased oil yield as well as net returns with B:C ratio. However, irrigation and nutrient had no significant effect on oil%. Both oil% and oil yield ha-1 was significantly increased up to 40 kg S ha-1 over 20 kg S ha-1. However, 20 kg S ha-1 fetched highest net returns as well as B:C ratio than 40 kg S ha-1. Combination of 0.8 IW/CPE and 150% RDF gave maximum oil yield and net returns but found at par with 1.0 IW/CPE and 150% RDF treatment combination.